Compensation, Job Stress, and Job Satisfaction on Nurse Turnover Intention at Ananda Bekasi Hospital - Novi Amanda; Rina Anindita; M. Reza Hilmy (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
One of the high turnover rates in the hospital occurs in nurses. More attention is needed because turnover can be detrimental to the organization, in terms of cost, resources, and effectiveness of nursing. The research objective is to obtain empirical evidence whether there is an effect of compensation, job stress and job satisfaction on turnover intention at Ananda Bekasi Hospital in 2020. The research method is to use causality design based on the time dimension of one short study. The sample used was saturated sampling, that is, the entire population was sampled for 100 inpatient nurses. The data analysis method uses Multiple Linear Regression Analysis. The results found no negative and significant effect between compensation for turnover intention. There is a positive and significant effect between work stress on turnover intention. There is a negative and significant effect between job satisfaction on turnover intention, and there is an influence between compensation, job stress and job satisfaction on turnover intention. Research findings, that the variable that most influences turnover intention is work stress variable. Managerial implications are expected Ananda Bekasi Hospital to calculate salaries based on the remuneration system, the appropriate assignment system, conduct workload analysis and nurse career development